Diagnosis of acute rheumatic fever - B. S. Belov; N. N. Kuzmina; L. G. Medyntseva; A. R. Babaeva; N. A. Shostak; E. V. Zhilyaev; S. E. Myasoedova; T. A. Raskina; S. P. Yakupova; V. N. Sorotskaya; E. N. Otteva (Научно-практическая ревматология, 2016)
Diagnosis of acute rheumatic fever.